Use of balneological methods in complex treatment of earlobe keloids - Таgunova, I. K.; Аndreev, A. V.; Gushcha, S. G.; Badiuk, N. S.; Gladkiy, T. V. (Journal of Education, Health and Sport, 2019)
Under certain conditions, skin damage may be accompanied by a complication in the form of hypertrophic scars, keloids. A significant role in the pathogenesis of the development of keloids is attributed to immune mechanisms, neuro-endocrine disorders, hereditary factors. The most effective way to treat keloid scars is still surgical. At the same time, simple excision of keloid stimulates additional collagen synthesis, increases the risk of relapse. Traditionally used steroid drugs, metered pressure, X-rays and radiotherapy. However, these methods can lead to undesirable consequences, which justifies the search for new, less aggressive methods. To increase the effectiveness of treatment of keloids of the earlobe using a new medical complex consisting of cryotherapy, a course of injections of the drug based on hyaluronidase and a course of drawing of sulphide-peloid extracts. A study of the state of keloid scar after cryodestruction and subsequent use of the drug based on hyaluronidase was carried out in 14 people. The cryoexposure was carried out by the two-cycle method with an exposure time of 30 to 90 s. To increase the efficiency and improve the performance in the complex treatment, a spinner made of silt-sulfide peloids was used, whose components stimulate collagen resorption by fibroclasts. As a result of treatment, all patients showed a significant improvement: subsidence of paresthesia, itching, leveling the height of keloid in relation to unchanged skin. Findings. The results obtained allow us to recommend the proposed method for the introduction into the practice of cosmetologists and otorhinolaryngologists.